A Modified Version of the Greek Simplified Medication Adherence Questionnaire for Hemodialysis Patients - Alikari, Victoria (Health Psychol Res, 2017)
Non-adherence to the therapeutic regimen is an increasingly growing problem especially among patients undergoing hemodialysis. The aim of this study was to modify the Greek version of Simplified Medication Adherence Questionnaire (GR-SMAQ) for patients undergoing hemodialysis (GR-SMAQ-HD) and explore its validity and reliability. Between June 2016 and November 2016 a group of patients undergoing hemodialysis (N=107) completed the Greek version of SMAQ. The study was carried out in three Dialysis Units of Hospitals of Athens and Peloponnese region, Greece. The form of GR-SMAQ was modified specifically for renal patients while four additional items were added so as the tool study all aspects of adherence to hemodialysis regimen. Construct validity was checked through exploratory factor analysis with principal Component Analysis with the Equamax method. Test-retest reliability and internal consistency were tested. Statistical analysis was performed using the IBM SPSS Statistics version 21. The significance level was set up at 5%. The Greek version of SMAQ for patients undergoing hemodialysis includes eight questions. Three factors emerged from factor analysis. Cronbach’s a coefficient was 0.742 for the whole scale and for each subscale was for Medication Adherence 0.75, for Attendance at hemodialysis session 0.856 and for Diet/Fluid restriction was 0.717. The total mean score was 6.29 (±1.82). GR-SMAQ-HD is a reliable and valuable tool that can be used by hemodialysis nurses and students of nursing for detection of adherence levels in clinical practice.